Connecting young star clusters to CO molecular gas in NGC 7793 with ALMA-LEGUS - Grasha, Kathryn; Grebel, Eva K.; Gouliermis, Dimitrios A. (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. We present an investigation of the relationship between giant molecular cloud (GMC) properties and the associated stellar clusters in the nearby floc
Gesehen am 25.01.2019